Summary of Research Activities during the 2021 Season of the EDEN ISS Antarctic Greenhouse - Bunchek, Jess; Vrakking, Vincent; Zabel, Paul; Schubert, Daniel; Dorn, Markus (2022)
Overview presentation about EDEN ISS mission of J. Bunchek (NASA/DLR).